Sexual identity and Gender Gap in Leadership. A political intention experiment - Evangelos Mourelatos; George Krimpas; Konstantinos Giotopoulos (Global Labor Organization (GLO), 2022)
The underrepresentation of women and homosexuals in leadership positions has been well documented, but the grounds for this need further investigation. We conduct a field and an online experiment to test a prominent theory about the sources of the sexual and gender gap in political leadership ambition: women's and homosexuals' higher aversion to engage to competitive environments. Within an experimental political environment as a context for our research, we employ two distinct subject sample pools - highly politically active individuals and workers from an online labor market. By controlling for a variety of internal and external factors and preference-based indicators, we establish that there are fundamental sexual and gender behavioral differences, stemming from differences in underlying psychological abilities and differences due to the nature of electoral competition. We find that priming individuals to consider the competitive nature of politics has a strong negative effect on women's and homosexuals' interest to run for a political office, but not on men's and heterosexuals' interest, hence significantly increasing the gender and sexual gap in leadership ambition. While on the online experiment the gender gap holds, surprisingly, we found that homosexuals' intention to participate in politics follows the opposite course.
Keywords: D01; D91; C93; 330; sexual gap; Gender gap; leadership; politics; experiment